Networks of Desire: How Technology Increases Our Passion to Consume - Kozinets, Robert; Patterson, Anthony; Ashman, Rachel (Journal of Consumer Research, 2017)
AbstractHow is consumer desire transformed by contemporary technology? Most extant theory holds that technology rationalizes and reduces passion. In our investigation of networks of desire—complex open systems of machines, consumers, energy, and objects—we find technology increasing the passion to consume. Effects depend upon participation in the network, which can be private, public, or professional. Private participation tends to discipline passion into interests reflecting established cultural categories. Public and professional participation build new connections between extant desires and a wider network, decentering ties and deterritorializing flows that limit hungers to emplaced bodies. Public and professional participation drive consumption passion to transgressive extremes. We use ethnography and netnography to study online food image sharing, a broad field that includes everything from friend networks to food bloggers. Using and extending Deleuze and Guattari’s desire theory, we conceptualize desire as energetic, connective, systemic, and innovative. Critically examining the role of technocapitalism in the realm of consumption passion, we question the emancipatory possibilities of unfettered desire. Networks of desire create a passionate new universe of technologically enhanced desire, one that challenges the way we think about consumer collectives, capitalism, emancipation, and posthuman consumption.